Facile One-Step Flame Synthesis of La1−xSrxMnO3 Nanoparticles for CO Catalytic Oxidation - Hao Zhou; Qiwei Wu; Boyang Qi (Journal of Chemistry)
A large amount of CO as hazardous emission in the iron ore sintering process has caused severe harm to the environment and human health. To control the emission of CO more effectively, the preparation of highly efficient catalysts has attracted much attention. In this study, the La1-xSrxMnO3 (0 ≤ x < 1) perovskite catalysts with different Sr2+ contents were prepared by the one-step flame synthesis method to treat CO pollutants in the iron and steel industry. The influence of Sr2+ doping on the structure and activity of catalytic were characterized and analyzed. La1-xSrxMnO3 perovskite catalysts exhibit good perovskite phases and loose spherical structures. The specific surface areas are between 4.1 and 12.0 m2 g−1. Combined with the results of H2-TPR and O2-TPD, the improvement of catalytic activity of La1-xSrxMnO3 perovskite can be attributed to the high concentration of active centers and oxygen vacancies. Significantly, the La0.4Sr0.6MnO3 catalyst presented the best reducibility and high content of absorbed active oxygen species, leading to a superior CO oxidation catalytic activity and reaches 50% CO conversion at 134.9°C and 90% at 163.2°C, respectively. The effects of water vapor and CO2 on the oxidation activity of La1-xSrxMnO3 perovskite was investigated. The flame-produced catalysts exhibit favorable catalytic stability and antisintering ability, achieving 100% CO conversion after fifth consecutive oxidation cycles.